Enhancing prospectives educators’ readiness through multidisciplinary collaboration in STEM education: an analysis of students enrolled in science and mathematics majors at a public university in Malaysia / Norezan Ibrahim ... [et al.] - Ibrahim, Norezan; Mohamed, Mawarni; Seshaiyer, Padmanabhan; Mohd Rasid, Nor Syazwani; Dalim, Siti Fairuz; Mat Salleh, Muhamad Furkan; Ismail, Mohamad Hisyam; Mohd Yusoff, Mohammad Mubarrak (Universiti Teknologi MARA, 2024)
Introducing successful STEM education in Malaysian educational institutions can aid in cultivating critical thinking skills among prospective educators, as STEM education is a pathway to acquiring 21st-century skills. By incorporating STEM courses into the curriculum through collaboration with industries, it helps to equip future teachers with the skills necessary to thrive and adapt in the evolving technological world. Aligned with the evolving landscape, this study aims to assess the readiness of future science and mathematics educators for STEM education. The key areas under examination encompass prospective teachers' individual teaching confidence and beliefs, expectations related to teaching outcomes, and attitudes toward 21st-century learning. These aspects will be measured across two distinct programs. This study involved 140 students majoring in Science and Mathematics and took STEM course from a faculty of education at a public higher institution in Malaysia. The participants have taken part in training sessions, including courses on the Internet of Things (IoT), hands-on educational tools, and Solar Energy, conducted in collaboration with STEM experts. The findings indicated a high level of personal teaching efficacy and belief, teaching outcome and expectancy beliefs, as well as 21st Century learning attitudes among prospective science and mathematics teachers. Therefore, engaging STEM experts and implementing a multidisciplinary teaching approach in STEM courses can enhance prospectives educators’ confidence and comprehension of STEM teaching.